Georgia's frontier women : female fortunes in a Southern colony - Marsh, Ben, 1976- (University of Georgia Press, 2007)
"Ranging from Georgia's founding in the 1730s until the American Revolution in the 1770s, Georgia's Frontier Women explores women's changing roles amid the developing demographic, economic, and social circumstances of the colony's settling." "Ben Marsh looks at the experiences of white, black, and Native American women - old and young, married and single, working in and out of the home. He also looks at how basic assumptions about courtship, marriage, and family varied over time."--BOOK JACKET.